Looking for Audience Costs in all the Wrong Places: Electoral Institutions, Media Access, and Democratic Constraint. (8th November 2013) - Potter, Philip B. K.; Baum, Matthew A.
<x content-type="archive" xml:space="preserve">Abstract</x> For leaders to generate credibility through audience costs, there must be mechanisms in place that enable citizens to learn about foreign policy failures. However, scholars have paid relatively little attention to variations among democracies in the extent to which the public is able to obtain this sort of information. We argue here that electoral institutions play this role by influencing the number of major political parties in a country and, with it, the extent and depth of opposition to the executive. Opposition leads to whistle-blowing, which makes it more likely that that the public will actually hear about a leader's foreign policy blunders. The effectiveness of this whistle-blowing, however, is conditional on the public's access to the primary conduit for communication between leaders and citizens: the mass media. We test these expectations statistically, demonstrating that leaders in systems with these attributes fare better with respect to their threats and the reciprocation of conflicts that they initiate. These findings suggest that democracies are not automatically able to generate credibility through audience costs and that the domestic institutions and political processes that link the public and leaders must be taken seriously.